2016
DOI: 10.1007/s00216-016-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography–atmospheric pressure laser ionization–mass spectrometry (LC-APLI-MS) analysis of polycyclic aromatic hydrocarbons with 6–8 rings in the environment

Abstract: A method has been developed for the sensitive and rapid analysis of polycyclic aromatic hydrocarbons (PAHs) in environmental samples using liquid chromatography time-of-flight mass spectrometry as well as the selective atmospheric pressure laser ionization (APLI) process (LC-APLI-MS). Upon analyzing 34 PAHs, the limits of detection of this method were found to range from 0.008 to 1.824 pg (0.024 pg for benzo[a]pyrene). The method therefore provides 30-fold to 5,400-fold increased sensitivity compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In 2017, they published a study in which polyaromatic hydrocarbons with six to eight aromatic rings were detected in environmental samples using liquid chromatography together with APLI and mass spectrometry. The reported sensitivity was 1000 times higher than in established GC‐MS applications (Thiäner & Achten, ). In the same year, they showed that GC‐APLI‐MS is not only sensitive and selective but also reliable by comparing measurements with certified reference material.…”
Section: Rempi‐msmentioning
confidence: 76%
“…In 2017, they published a study in which polyaromatic hydrocarbons with six to eight aromatic rings were detected in environmental samples using liquid chromatography together with APLI and mass spectrometry. The reported sensitivity was 1000 times higher than in established GC‐MS applications (Thiäner & Achten, ). In the same year, they showed that GC‐APLI‐MS is not only sensitive and selective but also reliable by comparing measurements with certified reference material.…”
Section: Rempi‐msmentioning
confidence: 76%
“…We reveal that the fragmentation-and background-free 87 detections by APLI 8,16 are also possible with a sub-…”
mentioning
confidence: 82%
“…Since the laser power 45 was stable enough during the experiments, the fluctuation of 46 the ion signal was satisfactorily small. However, the limit of 47 detection was far from that achieved by the established 48 APLI methods8,16 applied for real environmental samples.49 For example, the limit of detection of PAHs achieved by 50 APLI with a time-of-flight MS was on the order of tens of 51 femtograms. 16 The unfavorable detection limit of the present 52 results was attributed to the very small volume of primary 53 ionization as well as the small cross section of multiphoton 54 ionization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional analysis methods for polycyclic aromatic hydrocarbons are of diversity from common separation technologies alone such as GC , HPLC and CE , and typical detection techniques alone such as UV and MS detection to hybrid methodologies combining separation and detection technologies such as GC–MS and HPLC–MS . Of these methodologies, GC–MS is prevailing because of its inherent merits in highly efficient and sensitive analysis of volatile and weakly polar PAHs.…”
Section: Introductionmentioning
confidence: 99%